Fe isotope fractionation between chalcopyrite and dissolved Fe during hydrothermal recrystallization: An experimental study at 350 °C and 500 bars. (1st March 2017) - Syverson, Drew D.; Luhmann, Andrew J.; Tan, Chunyang; Borrok, David M.; Ding, Kang; Seyfried, William E.
Abstract: Equilibrium Fe isotope fractionation between chalcopyrite and dissolved Fe was determined in acidic chloride-bearing fluid at 350 °C and 500 bars. The study utilized deformable gold-cell technology, which allowed time-series sampling of solution during chalcopyrite recrystallization and isotope exchange. A key element of the experimental design involved the addition of anomalous dissolved 57 Fe to an on-going experiment as a means of determining the degree and rate of isotope exchange. Taking explicit account of imposed chemical and isotopic mass balance constraints of Fe in fluid and mineral (chalcopyrite) reservoirs, these data indicate that no more than 1000 h is required for the isotopically anomalous dissolved Fe reservoir to exchange completely with the coexisting chalcopyrite. The experimental calibration of the rate of Fe isotope exchange for the δ 57 Fe-spiked experiment provides critical insight for the time necessary to achieve Fe isotope exchange in two non-spiked, but otherwise identical experiments. The Fe isotope data indicate that the equilibrium fractionation between chalcopyrite and dissolved Fe, Δ 56 FeCpy-Fe (aq), at 350 °C is small, 0.09 ± 0.17‰ (2 σ ), and is in good agreement with recent theoretical equilibrium predictions. Owing to the apparent rate of Fe isotope exchange at 350 °C, it is likely that chalcopyrite formed at high temperature deep-sea vents (black smoker systems) achieves isotopic equilibrium, and effectively records the Fe isotopic composition of the coexisting end-member hydrothermal fluid. Comparison of the experimental mineral– fluid equilibrium fractionation factors with conjugate chalcopyrite and dissolved Fe pairs sampled from high temperature hydrothermal vent systems at Axial Caldera and Main Endeavour Field (Juan de Fuca Ridge) are in agreement with this inference. The experimental data were further used to determine the mineral– mineral equilibrium Fe isotope fractionation between pyrite-chalcopyrite, Δ 56 FePyr-Cpy, at 350 °C by combining previously determined pyrite-Fe 2+ (aq) equilibrium fractionation data with chalcopyrite-Fe 2+ (aq) from this study. The empirically determined Δ 56 FePyr-Cpy value, 0.90 ± 0.34‰ (2 σ ), is consistent with theoretical predictions, and when coupled with mineral– fluid Fe isotope fractionation systematics and experimentally determined exchange rates, helps to delineate processes of sulfide mineralization in hydrothermal systems.